Nonverbal communication in remote education: a literature review - Castillo Gil, Cecilia Isabel (2024)
Education, in pandemic, underwent major transformations due to the rapid and unprepared move from face-to-face to remote teaching.  New forms of communication were required to maintain student interest, motivation and participation in class.  Therefore, the objective of the present research was to analyze the theoretical bases linked to nonverbal communication and remote education, based on a literature review, of 60 articles published in databases such as Scopus, Scielo, Dialnet, Google Scholar, conducted between the years 2020 and 2022, in the field of higher education, from which 26 were selected.  The results show the need for greater teacher knowledge of the various aspects of non-verbal communication, through the computer, to avoid behaviors that constitute barriers to the teaching-learning process. Among the main conclusions is that nonverbal communication has a great influence on the reception of the content, participation and involvement of the student.